Continuing the multiple sclerosis risk sharing scheme is unjustified. (3rd June 2010) - McCabe, Christopher; Chilcott, Jim; Claxton, Karl; Tappenden, Paul; Cooper, Cindy; Roberts, Jennifer; Cooper, Nicola; Abrams, Keith
Abstract : Christopher McCabe and colleagues examine the claims behind the decision not to reduce drug costs in the multiple sclerosis risk sharing scheme